Answer:
[tex]g(x) = 3 |x - 5| + 3[/tex]
Step-by-step explanation:
Lets suppose that : y = f(x)
translating to the right:
(moving the graph to the right)
[tex]y = f(x - a)[/tex]
where: a>0
translating to the left:
(moving the graph to the left)
[tex]y = f(x - ( - a)) = f(x + a)[/tex]
where: a>0
translating up:
(moving the graph up)
[tex]y = f(x) + b[/tex]
where: b>0
translating down:
(moving the graph down)
[tex]y = f(x) - b[/tex]
where: b>0
So, in our case:
h(x) = 3 | x - 2 | + 4
*translating 3 to the right , 1 down
g(x) = h( x - 3 ) - 1
g(x) = 3 | x - 3 - 2 | + 4 - 1
g(x) = 3 | x - 5 | + 3